Lattice specific heat for the RMIn5 (R=Gd, La,Y; M=Co, Rh) compounds: Non-magnetic contribution subtraction - Facio, J.I.; Betancourth, D.; Cejas Bolecek, N.R.; Jorge, G.A.; Pedrazzini, P.; Correa, V.F.; Cornaglia, P.S.; Vildosola, V.; García D.J.; Correa, Víctor Félix; Pedrazzini, Pablo (Elsevier, 2016)
Fil: Facio, J.I. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina; Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina